Release film and method for producing release film
The release film with a specialized silicone resin composition and structure addresses poor releasability at non-180° angles and speed-dependent peeling forces, providing consistent and efficient peeling performance across different speeds.
Patent Information
- Application Number
- JP2021159437
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-29
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-09-29
AI Technical Summary
Conventional release films exhibit poor releasability at peeling angles less than 180° and varying peeling forces with changes in peeling speed, with existing technologies not addressing these issues effectively.
A release film comprising a base material layer and a release layer with a specific composition of high and low molecular weight silicone resins crosslinked by a crosslinking agent, optimized for peeling angles of 170°, featuring a controlled amount of silicon atoms and optional anchor coat layer, to enhance peeling performance at varying speeds.
The release film achieves excellent peeling performance at 170° with low peeling forces at both low and high speeds, reducing variations in peeling force due to speed changes, and ensuring easy removal from adhesive surfaces.
Smart Images

Figure 0007601737000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a release film and a method for producing a release film. [Background technology]
[0002] Conventionally, a release film has been laminated on a pressure-sensitive adhesive sheet in order to protect the adhesive surface, etc. As such a release film, for example, Patent Document 1 discloses a release sheet comprising a substrate and a release agent layer provided on at least one side of the substrate, the substrate being made of a plastic film, the elastic modulus of the release sheet measured from the side of the release agent layer opposite the substrate using an atomic force microscope being 1.5 MPa or more and 5.0 MPa or less, and the thickness of the release agent layer being 0.3 μm or more and 1.0 μm or less. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 6714387 Summary of the Invention [Problem to be solved by the invention]
[0004] Patent Document 1 discloses that the release film having the above-mentioned structure exhibits excellent releasability in a 180° peel test at a low speed of 300 mm / min. However, in actual peeling, the release film is rarely peeled at 180°, and is often peeled at an angle of about 170° or less. In addition, the releasability of conventional release films is easily affected by the peel angle, but Patent Document 1 does not consider releasability at angles of 170° or less. The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a release film having excellent releasability in a 170° peel test at a low speed. [Means for solving the problem]
[0005] The release film according to the embodiment of the present invention that can solve the above problems is as follows. [1] A base material layer, A release layer provided on at least one surface of the base layer, the release layer comprises a high-molecular-weight silicone resin (A1) having a number-average molecular weight of 250,000 or more and 1,300,000 or less, and a low-molecular-weight silicone resin (B1) having a number-average molecular weight of 1,000 or more and 200,000 or less, the high-molecular-weight silicone resin (A1) and / or the low-molecular-weight silicone resin (B1) being crosslinked with a crosslinking agent; A release film, characterized in that the silicon atomic weight in the release layer, as measured by fluorescent X-ray analysis, is 4 kcps or more and 40 kcps or less.
[0006] The above-mentioned configuration makes it possible to provide a release film that has excellent releasability in 170° peeling at a low speed. A preferred embodiment of the release film is as follows: [2] to [6]. A preferred embodiment of the method for producing the release film is as follows: [7]. [2] The release film according to [1], wherein a standard acrylic adhesive tape TESA7475 is attached to the release layer in an environment having a temperature of 10 to 30°C and a relative humidity of 30 to 80%, and then allowed to stand for 20 hours, and then a peel test is performed in an environment having a temperature of 18 to 22°C and a relative humidity of 61 to 69%, in which the peel force F1 is 100 mN / 25 mm or less in a peel test in which a 170° peel is performed at a tensile speed of 300 mm / min. [3] The release film according to [1] or [2], wherein a standard acrylic adhesive tape TESA7475 is attached to the release layer in an environment having a temperature of 10 to 30°C and a relative humidity of 30 to 80%, and then allowed to stand for 20 hours, and then a peel test is performed in an environment having a temperature of 18 to 22°C and a relative humidity of 61 to 69%, in which the peel force F2 is 5.0 N / 25 mm or less in a peel test in which a 20° peel is performed at a tensile speed of 10,000 mm / min. [4] The release film according to any one of [1] to [3], in which a standard acrylic adhesive tape, Nitto 31B, is attached to the release layer in an environment having a temperature of 10 to 30° C. and a relative humidity of 30 to 80%, and then the tape is left to stand for 20 hours, and then a peel force F3 (N / 25 mm) in a peel test in which 170° peeling is performed at a tensile speed of 1,500 mm / min in an environment having a temperature of 18 to 22° C. and a relative humidity of 61 to 69% is performed, and a peel force F4 (N / 25 mm) in a peel test in which 170° peeling is performed at a tensile speed of 30,000 mm / min satisfies the following formula (1): F4 / F3≦4.0 (1) [5] The release film according to any one of [1] to [4], wherein the high molecular weight silicone resin (A1) has an alkylene group having 3 or more and 12 or less carbon atoms at a crosslinking point, and does not have an alkylene group having 2 or less carbon atoms at a crosslinking point. [6] The release film according to any one of [1] to [5], which has an anchor coat layer between the base layer and the release layer. [7] A step of preparing a coating liquid by mixing a high molecular weight silicone resin (A2) having a number average molecular weight of 250,000 or more and 1,300,000 or less, a low molecular weight silicone resin (B2) having a number average molecular weight of 1,000 or more and 200,000 or less, a catalyst, a crosslinking agent, and an organic solvent; A step of applying the coating liquid to one surface of a substrate layer to form a coating film; and A method for producing a release film, comprising the step of curing the coating film to form a release layer. Effect of the Invention
[0007] According to the present invention, with the above-mentioned configuration, it is possible to provide a release film that has excellent releasability when peeled off at 170° at a low speed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] A release film according to an embodiment of the present invention has a base layer and a release layer provided on at least one surface of the base layer, the release layer containing a high molecular weight silicone resin (A1) having a number average molecular weight of 250,000 or more and 1,300,000 or less and a low molecular weight silicone resin (B1) having a number average molecular weight of 1,000 or more and 200,000 or less, the high molecular weight silicone resin (A1) and / or the low molecular weight silicone resin (B1) being crosslinked with a crosslinking agent, and the silicon atomic weight in the release layer as measured by X-ray fluorescence analysis is 4 kcps or more and 40 kcps or less.
[0009] The above-mentioned configuration can improve the releasability in 170° peeling at a low speed. Each configuration of the release film according to the embodiment will be described in detail below. In this specification, the resins, additives, solvents, etc. exemplified can be used alone or in combination unless otherwise specified.
[0010] The substrate layer is preferably one that can provide a release layer on at least one surface. Examples of the substrate layer include resin films and paper sheets. The resin film is preferably a biaxially stretched resin film. Examples of the resin film include polyester films, polyolefin films, polycarbonate films, polyvinyl acetate films, and the like. Examples of the polyester film include films containing polyesters such as polyethylene terephthalate and polyethylene naphthalate, and films made of polyesters. Examples of the polyolefin film include films containing polyolefins such as polypropylene and polymethylpentene, and films made of polyolefins. Among these, polyester films are preferred, polyethylene terephthalate films are more preferred, and biaxially stretched polyethylene terephthalate films are even more preferred. Examples of the paper sheet include paper sheets such as fine paper, coated paper, glassine paper, kraft paper, and polyethylene laminated paper. The substrate layer may be a single layer or a multilayer. In the case of a multilayer, two or more layers may be laminated.
[0011] At least one surface of the substrate layer may be subjected to a treatment for improving adhesion to the release layer, such as a corona discharge treatment, a plasma discharge treatment, a chromium oxidation treatment, a flame treatment, a hot air treatment, an ozone treatment, an ultraviolet irradiation treatment, a sandblasting treatment, a thermal spraying treatment, a primer treatment, etc.
[0012] The thickness of the substrate layer is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, even more preferably 20 μm or more, and is preferably 300 μm or less, more preferably 200 μm or less, even more preferably 125 μm or less, and even more preferably 80 μm or less.
[0013] The release layer contains a high molecular weight silicone resin (A1) having a number average molecular weight of 250,000 or more and 1,300,000 or less, and a low molecular weight silicone resin (B1) having a number average molecular weight of 1,000 or more and 200,000 or less, and the high molecular weight silicone resin (A1) and / or the low molecular weight silicone resin (B1) are crosslinked with a crosslinking agent. It is preferable that at least the high molecular weight silicone resin (A1) is crosslinked with a crosslinking agent, and it is more preferable that the high molecular weight silicone resin (A1) and the low molecular weight silicone resin (B1) are crosslinked with a crosslinking agent.
[0014] The number average molecular weight of the high molecular weight silicone resin (A1) is 250,000 or more and 1,300,000 or less. This can improve the releasability. The number average molecular weight is preferably 300,000 or more, more preferably 350,000 or more, even more preferably more than 400,000, even more preferably 410,000 or more, particularly preferably 430,000 or more, and preferably 1,000,000 or less, more preferably 800,000 or less, even more preferably 600,000 or less, even more preferably 550,000 or less, and particularly preferably 500,000 or less. When the high molecular weight silicone resin (A1) contains an alkylene group at the crosslinking point, the number average molecular weight is the molecular weight including the alkylene group. In addition, the number average molecular weight is preferably a polystyrene-equivalent value measured by gel permeation chromatography (GPC).
[0015] As the high molecular weight silicone resin (A1), polyorganosiloxane is preferred. As the polyorganosiloxane, polydimethylsiloxane, polyphenylmethylsiloxane, polydiphenylsiloxane, etc. are preferred, and polydimethylsiloxane is more preferred.
[0016] The high molecular weight silicone resin (A1) preferably has an alkylene group having 3 to 12 carbon atoms at the crosslinking point. Furthermore, the high molecular weight silicone resin (A1) preferably has an alkylene group having 3 to 12 carbon atoms at the crosslinking point, and does not have an alkylene group having 2 or less carbon atoms at the crosslinking point. This can improve the releasability at low and high speed peeling. Furthermore, the releasability can be improved at a peel angle of about 20°. Furthermore, the variation in peel force due to the change in peeling speed can be reduced. The alkylene group preferably has 3 to 12 carbon atoms, more preferably has 4 to 10 carbon atoms, even more preferably has 5 to 8 carbon atoms, and most preferably has 6 carbon atoms. The alkylene group may be branched, but is preferably linear. Specific examples of the alkylene group include linear alkylene groups such as trimethylene, tetramethylene, pentamethylene, hexamethylene, heptamethylene, octamethylene, nonamethylene, decamethylene, undecamethylene, and dodecamethylene; and branched alkylene groups such as methylethylene, methyltrimethylene, methyltetramethylene, methylpentamethylene, methylhexamethylene, methylheptamethylene, methyloctamethylene, methylnonamethylene, methyldecamethylene, and methylundecamethylene. In addition, it is preferable that the high molecular weight silicone resin (A1) does not have an alkylene group having 13 or more carbon atoms at the crosslinking point.
[0017] The number average molecular weight of the low molecular weight silicone resin (B1) is 1,000 or more and 200,000 or less. This can improve the releasability. The number average molecular weight is preferably 2,000 or more, more preferably 3,000 or more, even more preferably 4,000 or more, even more preferably 5,000 or more, particularly preferably 7,000 or more, and is preferably 150,000 or less, more preferably 100,000 or less, even more preferably 60,000 or less, even more preferably 30,000 or less, particularly preferably 20,000 or less. When the low molecular weight silicone resin (B1) contains an alkylene group at the crosslinking point, the number average molecular weight is the molecular weight including the alkylene group. In addition, the number average molecular weight is preferably a polystyrene-equivalent value measured by gel permeation chromatography (GPC).
[0018] The low molecular weight silicone resin (B1) is preferably a polyorganosiloxane. As the polyorganosiloxane, polydimethylsiloxane, polyphenylmethylsiloxane, polydiphenylsiloxane, etc. are preferred, and polydimethylsiloxane is more preferred.
[0019] The low molecular weight silicone resin (B1) preferably has an alkylene group having 2 or more and 5 or less carbon atoms at the crosslinking point. This can improve the releasability. The alkylene group preferably has 2 or more and 5 or less carbon atoms, more preferably has 2 or more and 4 or less carbon atoms, even more preferably has 2 or more and 3 or less carbon atoms, and most preferably has 2 carbon atoms. The alkylene group may be branched, but is preferably linear. Specific examples of the alkylene group include linear alkylene groups such as dimethylene group, trimethylene group, tetramethylene group, and pentamethylene group; and branched alkylene groups such as methylethylene group, methyltrimethylene group, and methyltetramethylene group. The low molecular weight silicone resin (B1) preferably does not have an alkylene group having 6 or more carbon atoms at the crosslinking point.
[0020] When the total solid content of the high molecular weight silicone resin (A1) and the low molecular weight silicone resin (B1) in the release layer is 10 parts by mass, the content of the low molecular weight silicone resin (B1) is preferably 2 parts by mass or more, more preferably 4 parts by mass or more, even more preferably 6 parts by mass or more, and even more preferably 8 parts by mass or more. This can improve the releasability in low speed and high speed peeling. It can also improve the releasability at a peel angle of about 20°. It can also reduce the variation in peel force caused by changes in peel speed. On the other hand, the content of the low molecular weight silicone resin (B1) is preferably 9.8 parts by mass or less, more preferably 9.6 parts by mass or less, even more preferably 9.4 parts by mass or less, and even more preferably 9.2 parts by mass or less. This can obtain a good coating appearance.
[0021] The number average molecular weight between crosslinking points of the crosslinked portion formed by the crosslinking agent is preferably 200 or more and 3,500 or less. This can improve the releasability. The number average molecular weight between crosslinking points is more preferably 400 or more and 3,000 or less, even more preferably 600 or more and 2,800 or less, and even more preferably 800 or more and 2,500 or less. The crosslinked portion is preferably formed by polyorganosiloxane.
[0022] The silicon atom weight in the release layer measured by fluorescent X-ray analysis is 4 kcps or more and 40 kcps or less. This can improve the releasability. The silicon atom weight is preferably 6 kcps or more, more preferably 8 kcps or more, and preferably 35 kcps or less, more preferably 30 kcps or less. The silicon atom weight can be measured by the method described in the examples below. The silicon atom weight in the release layer can be adjusted by controlling the amount of silicone resin.
[0023] In 100% by mass of the release layer, the total content of the high molecular weight silicone resin (A1) and the low molecular weight silicone resin (B1) is preferably 75% by mass or more, more preferably 80% by mass or more, even more preferably 85% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more. Meanwhile, the total amount may be 98% by mass or less, 95% by mass or less, or 92% by mass or less. The content includes the crosslinked portion crosslinked by the crosslinking agent.
[0024] The release layer may contain additives such as catalysts, lubricants, adhesion improvers, and light release adjusters. In 100% by mass of the release layer, the content of the additives is preferably 2% by mass or more, more preferably 5% by mass or more, and even more preferably 8% by mass or more. On the other hand, the content of the additives is preferably 25% by mass or less, more preferably 20% by mass or less, even more preferably 15% by mass or less, and even more preferably 10% by mass or less.
[0025] The catalyst can be referred to in the description of the manufacturing method described later. Examples of the lubricant include inorganic particles and organic particles. Examples of the inorganic particles include particles containing inorganic substances such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, and more preferably particles made of inorganic substances. Examples of the organic particles include particles containing organic substances such as thermosetting urea resin, thermosetting phenolic resin, thermosetting epoxy resin, benzoguanamine resin, and silicone resin, and more preferably particles made of organic substances. Examples of the adhesion improver include organosilicon compounds containing reactive groups. Examples of the reactive groups include epoxy groups, mercapto groups, (meth)acryloyl groups, haloalkyl groups, and amino groups. Examples of the light release adjuster include silicone oil.
[0026] The release layer has a basis weight of 0.1 g / m 2 It is preferable that the weight per unit area is 0.2 g / m or more. 2More preferably, it is 0.3 g / m or more. 2 More preferably, it is 0.4 g / m or more. 2 It is even more preferable that the basis weight is 2.0 g / m or more. 2 It is preferable that the content is 1.5 g / m or less. 2 More preferably, it is 1.0 g / m or less. 2 It is more preferable that the thickness is equal to or less than 100 mm. This can improve the releasability.
[0027] The release film preferably has an anchor coat layer between the base layer and the release layer. The anchor coat layer can be formed by applying an anchor coat agent to the surface of the base layer on the release layer side. Examples of the anchor coat agent include polyester resins, urethane resins, acrylic resins, oxazoline group-containing resins, carbodiimide group-containing resins, epoxy group-containing resins, isocyanate-containing resins, and copolymers thereof, and coating agents mainly composed of natural rubber and synthetic rubber. The thickness of the anchor coat layer is preferably 0.005 μm or more and 5 μm or less, and more preferably 0.01 μm or more and 1 μm or less.
[0028] The release film is preferably a release force F1 of 100 mN / 25 mm or less in a peel test in which a standard acrylic adhesive tape TESA7475 is attached to the release layer in an environment of a temperature of 10 to 30° C. and a relative humidity of 30 to 80% RH, and then the release film is left standing for 20 hours in an environment of a temperature of 18 to 22° C. and a relative humidity of 61 to 69% RH, and the release film is peeled at 170° at a tensile speed of 300 mm / min. This makes it easier to peel the release film at a low speed. The peel force F1 is more preferably 95 mN / 25 mm or less, even more preferably 90 mN / 25 mm or less, even more preferably 80 mN / 25 mm or less, particularly preferably 70 mN / 25 mm or less, and most preferably 60 mN / 25 mm or less. On the other hand, the peel force F1 may be 10 mN / 25 mm or more, or may be 20 mN / 25 mm or more. The peel force F1 (mN / 25 mm) is measured so that the width of the contact area between the release film and the standard acrylic adhesive tape TESA7475 is 25 mm.
[0029] The release film preferably has a peeling force F2 of 5.0 N / 25 mm or less in a peeling test in which a standard acrylic adhesive tape TESA7475 is attached to the release layer in an environment of a temperature of 10 to 30° C. and a relative humidity of 30 to 80% RH, and then the standard acrylic adhesive tape is left standing for 20 hours in an environment of a temperature of 18 to 22° C. and a relative humidity of 61 to 69% RH, and 20° peeling is performed at a tensile speed of 10,000 mm / min. This makes it easier to peel the release film at high speed. This also makes it easier to peel the release film from the end. The peeling force F2 is more preferably 4.5 N / 25 mm or less, even more preferably 4.0 N / 25 mm or less, even more preferably 3.5 N / 25 mm or less, and particularly preferably 3.0 N / 25 mm or less. On the other hand, the peeling force F2 may be 0.5 N / 25 mm or more, or 1.0 N / 25 mm or more. The peel force F2 (N / 25 mm) is measured so that the width of the contact area between the release film and the standard acrylic adhesive tape TESA7475 is 25 mm.
[0030] The release film is preferably prepared by attaching a standard acrylic adhesive tape Nitto 31B to the release layer in an environment of 10 to 30°C and 30 to 80%RH relative humidity for 20 hours, and then in an environment of 18 to 22°C and 61 to 69%RH relative humidity, the peel force F3 (N / 25mm) in a peel test in which 170° peeling is performed at a tensile speed of 1500mm / min and 30,000mm / min and the peel force F4 (N / 25mm) in a peel test in which 170° peeling is performed at a tensile speed of 30,000mm / min satisfy the following formula (1). The measurements of the peel force F3 (N / 25mm) and the peel force F4 (N / 25mm) are performed so that the width of the contact area between the release film and the standard acrylic adhesive tape Nitto 31B is 25mm. F4 / F3≦4.0 (1)
[0031] This can reduce the variation in peel force caused by changes in peel speed. The value of the left side of formula (1) is more preferably 3.5 or less, even more preferably 3.0 or less, and even more preferably 2.7 or less. On the other hand, the value of the left side of formula (1) may be 1.0 or more, may be more than 1.0, or may be 1.5 or more.
[0032] The peeling force F3 is preferably 0.07 N / 25 mm or less, more preferably 0.06 N / 25 mm or less, and even more preferably 0.05 N / 25 mm or less. This makes it easier to peel off the release film at a medium speed. On the other hand, the peeling force F3 may be 0.01 N / 25 mm or more.
[0033] The peeling force F4 is preferably 0.20 N / 25 mm or less, more preferably 0.18 N / 25 mm or less, and even more preferably 0.13 N / 25 mm or less. This makes it easier to peel off the release film at high speed. On the other hand, the peeling force F4 may be 0.03 N / 25 mm or more.
[0034] The release film can be used as a protective film for protecting the adhesive surface of labels, stickers, double-sided tapes, adhesive materials, etc., and as a protective material when manufacturing liquid crystal display parts, printed wiring boards, etc. In particular, it can be preferably used for protecting the surface of acrylic adhesives.
[0035] The method for producing a release film according to an embodiment of the present invention includes the steps of: mixing a high molecular weight silicone resin (A2) having a number average molecular weight of 250,000 or more and 1,300,000 or less, a low molecular weight silicone resin (B2) having a number average molecular weight of 1,000 or more and 200,000 or less, a catalyst, a crosslinking agent, and an organic solvent to prepare a coating liquid; applying the coating liquid to one side of a substrate layer to form a coating film; and curing the coating film to form a release layer.
[0036] The number average molecular weight of the high molecular weight silicone resin (A2) is 250,000 or more and 1,300,000 or less. This can improve the releasability. The number average molecular weight is preferably 300,000 or more, more preferably 350,000 or more, even more preferably more than 400,000, even more preferably 410,000 or more, particularly preferably 430,000 or more, and preferably 1,000,000 or less, more preferably 800,000 or less, even more preferably 600,000 or less, even more preferably 550,000 or less, and particularly preferably 500,000 or less. The number average molecular weight is preferably a polystyrene-equivalent value measured by gel permeation chromatography (GPC).
[0037] As the high molecular weight silicone resin (A2), polyorganosiloxane is preferred. As the polyorganosiloxane, polydimethylsiloxane, polyphenylmethylsiloxane, polydiphenylsiloxane, etc. are preferred, and polydimethylsiloxane is more preferred.
[0038] The high molecular weight silicone resin (A2) preferably has a reactive functional group capable of reacting with the reactive functional group of the crosslinking agent. The high molecular weight silicone resin (A2) may have a reactive functional group at one end or both ends, or may have a reactive functional group in a side chain. The reactive functional group is preferably an alkenyl group or a hydrosilyl group, and more preferably an alkenyl group. The alkenyl group preferably has 3 or more and 12 or less carbon atoms, more preferably has 4 or more and 10 or less carbon atoms, further preferably has 5 or more and 8 or less carbon atoms, and most preferably has 6 carbon atoms. The alkenyl group may be branched, but is preferably linear. Specific examples of linear alkenyl groups include a propenyl group, a butenyl group, a pentenyl group, a hexenyl group, a heptenyl group, an octenyl group, a nonenyl group, a decenyl group, an undecenyl group, and a dodecenyl group.
[0039] The high molecular weight silicone resin (A2) preferably has an alkenyl group having 3 or more and 12 or less carbon atoms, and preferably has an alkenyl group having 3 or more and 12 or less carbon atoms and does not have an alkenyl group having 2 or less carbon atoms. Furthermore, the high molecular weight silicone resin (A2) preferably does not have an alkenyl group having 13 or more carbon atoms. Furthermore, the high molecular weight silicone resin (A2) does not need to have a hydrosilyl group.
[0040] The number average molecular weight of the low molecular weight silicone resin (B2) is 1,000 or more and 200,000 or less. This can improve the releasability. The number average molecular weight is preferably 2,000 or more, more preferably 3,000 or more, even more preferably 4,000 or more, even more preferably 5,000 or more, particularly preferably 7,000 or more, and is preferably 150,000 or less, more preferably 100,000 or less, even more preferably 60,000 or less, even more preferably 30,000 or less, particularly preferably 20,000 or less. The number average molecular weight is preferably a polystyrene-equivalent value measured by gel permeation chromatography (GPC).
[0041] As the low molecular weight silicone resin (B2), polyorganosiloxane is preferable. As the polyorganosiloxane, polydimethylsiloxane, polyphenylmethylsiloxane, polydiphenylsiloxane, etc. are preferable, and polydimethylsiloxane is more preferable.
[0042] The low molecular weight silicone resin (B2) preferably has a reactive functional group capable of reacting with the reactive functional group of the crosslinking agent. The low molecular weight silicone resin (B2) may have a reactive functional group at one end or both ends, or may have a reactive functional group in a side chain. The reactive functional group is preferably an alkenyl group or a hydrosilyl group, and more preferably an alkenyl group. The alkenyl group preferably has 2 to 5 carbon atoms, more preferably has 2 to 4 carbon atoms, even more preferably has 2 to 3 carbon atoms, and most preferably has 2 carbon atoms. That is, the most preferred is a vinyl group. The alkenyl group may be branched, but is preferably linear. Specific examples of linear alkenyl groups include vinyl groups, propenyl groups, butenyl groups, pentenyl groups, hexenyl groups, heptenyl groups, octenyl groups, nonenyl groups, decenyl groups, undecenyl groups, and dodecenyl groups. The low molecular weight silicone resin (B2) preferably does not have an alkenyl group having a carbon number of 6 or more. The low molecular weight silicone resin (B2) may not have a hydrosilyl group.
[0043] The crosslinking agent preferably has two or more reactive functional groups in one molecule that can react with the reactive functional groups of the high molecular weight silicone resin (A2) and / or the low molecular weight silicone resin (B2). The crosslinking agent may have a reactive functional group at one end or both ends, or may have a reactive functional group in a side chain. The reactive functional group is preferably an alkenyl group or a hydrosilyl group, and more preferably a hydrosilyl group. As the alkenyl group, an alkenyl group having 2 or more and 12 or less carbon atoms is preferred, an alkenyl group having 2 or more and 10 or less carbon atoms is more preferred, an alkenyl group having 2 or more and 8 or less carbon atoms is even more preferred, and an alkenyl group having 2 or more and 6 or less carbon atoms is most preferred. The alkenyl group may be branched, but is preferably linear. As the crosslinking agent, a polyorganosiloxane having a reactive functional group is preferred, and a polyorganosiloxane having a hydrosilyl group is more preferred.
[0044] Examples of polyorganosiloxanes having hydrosilyl groups include dimethylsiloxane-methylhydrosiloxane copolymer, diphenylsiloxane-phenylhydrosiloxane copolymer, polyethylhydrosiloxane, methylhydrosiloxane-phenylmethylsiloxane copolymer, methylhydrosiloxane-octylmethylsiloxane copolymer, hydrosilyl group-containing methylsilicone resin, and polyphenyl(dimethylhydrosiloxy)siloxane.
[0045] The number average molecular weight of the crosslinking agent is preferably 200 or more and 3,500 or less. This can improve the releasability. The number average molecular weight of the crosslinking agent is more preferably 400 or more and 3,000 or less, even more preferably 600 or more and 2,800 or less, and even more preferably 800 or more and 2,500 or less. The number average molecular weight of the crosslinking agent is preferably smaller than the number average molecular weight of the low molecular weight silicone resin (B2).
[0046] When the total solid content of the high molecular weight silicone resin (A2) and the low molecular weight silicone resin (B2) in the coating liquid is 10 parts by mass, the content of the low molecular weight silicone resin (B2) is preferably 2 parts by mass or more, more preferably 4 parts by mass or more, even more preferably 6 parts by mass or more, and even more preferably 8 parts by mass or more. On the other hand, the content of the low molecular weight silicone resin (B2) is preferably 9.8 parts by mass or less, more preferably 9.6 parts by mass or less, even more preferably 9.4 parts by mass or less, and even more preferably 9.2 parts by mass or less.
[0047] In the coating liquid, the total content of the high molecular weight silicone resin (A2), the low molecular weight silicone resin (B2), and the crosslinking agent is preferably 75% by mass or more, more preferably 80% by mass or more, even more preferably 85% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more, based on 100% by mass of the solid content. On the other hand, the total amount may be 98% by mass or less, 95% by mass or less, or 92% by mass or less.
[0048] The content of the crosslinking agent in the coating liquid is preferably 0.5 parts by mass or more, more preferably 1.5 parts by mass or more, based on 100 parts by mass of the total of the high molecular weight silicone resin (A2) and the low molecular weight silicone resin (B2), while the content of the crosslinking agent is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 4 parts by mass or less.
[0049] The catalyst is preferably a hydrosilylation catalyst. The hydrosilylation catalyst is preferably a platinum catalyst, a palladium catalyst, or a rhodium catalyst, and more preferably a platinum catalyst. Examples of the platinum catalyst include fine particles of platinum, fine particles of platinum adsorbed on a carbon powder carrier, chloroplatinic acid, alcohol-modified chloroplatinic acid, and an olefin complex of chloroplatinic acid. Examples of the palladium catalyst include tetrakis(triphenylphosphine)palladium, etc. Examples of the rhodium catalyst include chlorotris(triphenylphosphine)rhodium, etc.
[0050] The catalyst content in the coating liquid is preferably 0.5 parts by mass or more, more preferably 1.5 parts by mass or more, based on 100 parts by mass of the total of the high molecular weight silicone resin (A2), the low molecular weight silicone resin (B2), and the crosslinking agent, while the catalyst content is preferably 6 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 4 parts by mass or less.
[0051] In addition to the catalyst, the coating liquid may contain additives such as the above-mentioned lubricant, adhesion improver, and light release adjuster. In 100% by mass of the solid content of the coating liquid, the content of the additive is preferably 2% by mass or more, more preferably 5% by mass or more, and even more preferably 8% by mass or more. On the other hand, the content of the additive is preferably 25% by mass or less, more preferably 20% by mass or less, even more preferably 15% by mass or less, and even more preferably 10% by mass or less.
[0052] Examples of the organic solvent include aliphatic hydrocarbon solvents and aromatic hydrocarbon solvents. Examples of the aliphatic hydrocarbon solvent include heptane, pentane, isopentane, hexane, isohexane, isoheptane, 2,2,4-trimethylpentane, octane, isooctane, cyclohexane, methylcyclohexane, and methyl isobutyl ketone, more preferably heptane and methyl isobutyl ketone, and even more preferably heptane. Examples of the aromatic hydrocarbon solvent include toluene and xylene, and more preferably toluene. The aliphatic hydrocarbon solvent and the aromatic hydrocarbon solvent may be mixed and used.
[0053] In 100% by mass of the coating liquid, the content of the organic solvent is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, while the content of the organic solvent is preferably 95% by mass or less, and more preferably 92% by mass or less.
[0054] Examples of the method for applying the coating liquid include gravure coating, bar coating, spray coating, spin coating, knife coating, roll coating, and die coating.
[0055] The coating film can be cured by drying. The drying is preferably performed by a heat treatment. The drying temperature is preferably 80°C or higher, more preferably 100°C or higher, and even more preferably 120°C or higher. This makes it easier for the hydrosilylation reaction to occur. On the other hand, the drying temperature is preferably 180°C or lower, more preferably 160°C or lower. This can reduce deterioration of the resin due to excessive heating. The drying time is preferably 20 seconds or longer, more preferably 40 seconds or longer. On the other hand, the drying time is preferably 120 seconds or shorter, more preferably 90 seconds or shorter. EXAMPLES
[0056] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples, and can be modified within the scope of the above and below mentioned aims, and all such modifications are included in the technical scope of the present invention.
[0057] <Measurement of silicon atomic weight> The silicon atom weight (kcps (counts per second)) in the release layer of the release film was measured by measuring the Si-Kα line intensity using a fluorescent X-ray analyzer Supermini 200 manufactured by Rigaku under the following conditions. X-ray source: Pd target ceramic tube Analysis area: 30mmφ Analysis element: Si Spectroscopic crystal: PET Output: 50kv, 4mA Measurement atmosphere: Vacuum The sample (area = 30 mmφ) was irradiated with excitation X-rays (ray source = Pd target ceramic tube, output = 50 kv, 4 mA), and the intensity of the fluorescent X-rays of Si dispersed by a dispersive crystal (= PET) was measured.
[0058] <Measurement of peeling force F1> A release film with a width of 30 mm and a length of 200 mm was prepared. Next, in an environment of a temperature of 23°C and a relative humidity of 50% RH, a standard acrylic adhesive tape TESA7475 with a width of 25 mm was attached to the release layer of the release film, and a 5000g rubber roller was moved back and forth at a speed of 100 mm / sec to press the film, and then the film was left standing for 20 hours. Then, in an environment of a temperature of 20°C and a relative humidity of 65% RH, a tensile tester (AG-50NX HS) manufactured by Shimadzu Corporation was used to perform 170° peeling at a tensile speed of 300 mm / min to measure the peel force F1 (mN / 25 mm).
[0059] <Measurement of peel force F2> The peel force F2 (N / 25 mm) was measured in the same manner as the peel force F1, except that the tensile speed was 10,000 mm / min, 20° peeling was performed, and a tensile testing machine (VPA-2) manufactured by Kyowa Interface Science Co., Ltd. was used.
[0060] <Measurement of peel force F3> The peel force F3 (N / 25 mm) was measured in the same manner as the peel force F1, except that the standard adhesive tape used was a 25 mm wide standard acrylic adhesive tape, Nitto 31B, the tensile speed was 1500 mm / min, and a tensile testing machine (VPA-2) manufactured by Kyowa Interface Science Co., Ltd. was used.
[0061] <Measurement of peel force F4> The peel force F4 (N / 25 mm) was measured in the same manner as the peel force F1, except that the standard adhesive tape used was a 25 mm wide standard acrylic adhesive tape, Nitto 31B, the tensile speed was 30,000 mm / min, and a tensile testing machine (VPA-2) manufactured by Kyowa Interface Science Co., Ltd. was used.
[0062] <Preparation of release film> The release films of Examples 1 to 7 and Comparative Example 1 were produced according to the following procedure.
[0063] Example 1 Organopolysiloxane LTC310 (number average molecular weight: 450,000) manufactured by Dow Toray Industries, Inc., as a high molecular weight silicone resin (A2), was dissolved in a mixed solvent of toluene and heptane (mass ratio 40:60) to obtain a silicone resin solution (A2) with a solid concentration of 20 mass%. Note that organopolysiloxane LTC310 is an organopolysiloxane that does not have a vinyl group but has a hexenyl group, and is mixed with organopolysiloxane (number average molecular weight: 2,000) that has a hydrosilyl group as a crosslinking agent.
[0064] Next, organopolysiloxane SL3832 (number average molecular weight: 10,000) manufactured by Momentive Corporation as a low molecular weight silicone resin (B2) and organopolysiloxane CL750 (number average molecular weight: 1,000) having a hydrosilyl group manufactured by Momentive Corporation as a crosslinking agent were dissolved in heptane in a mass ratio of 97:3 to obtain a silicone resin solution (B2) having a solid content concentration of 20 mass%. Organopolysiloxane SL3832 is a polydimethylsiloxane having a vinyl group.
[0065] Next, 10 parts by mass of the silicone resin solution (A2) and 90 parts by mass of the silicone resin solution (B2) were dissolved in a mixed solvent of heptane and methyl isobutyl ketone (mass ratio 80:20) to obtain a solution with a solid content concentration of 14% by mass. Furthermore, 3 parts by mass of Momentive's platinum-based catalyst (CM678) with a concentration of 100% by mass was added and mixed to obtain a coating liquid for forming a release layer.
[0066] Next, the obtained coating liquid was applied to one side of a 50 μm-thick biaxially oriented polyethylene terephthalate film (E5100) manufactured by Toyobo Co., Ltd. as a base layer using a bar coater. The coating film was then dried by heating at 150° C. for 1 minute to harden the coating film, thereby obtaining a release film in which a release layer was formed on one side of the base layer. In addition, in the coating, the coating amount was adjusted so that the silicon atom amount contained in the release layer after drying of the silicone resin was 10 kcps as measured by fluorescent X-ray analysis.
[0067] [Examples 2 and 3, Comparative Example 1] A release film was obtained in the same manner as in Example 1, except that the coating amount was changed so that the amount of silicon atoms contained in the release layer was the amount shown in Table 1.
[0068] [Examples 5 to 7] A release film was obtained in the same manner as in Example 1, except that the mixing ratio of the silicone resin solution (A2) and the silicone resin solution (B2) was changed so that the solid content mixing ratio of the high molecular weight silicone resin (A2) and the low molecular weight silicone resin (B2) was the solid content mixing ratio shown in Table 1.
[0069] Example 4 Organopolysiloxane LTC755 (number average molecular weight: 450,000) manufactured by Dow Toray Industries, Inc. was dissolved in a mixed solvent of toluene and heptane (mass ratio 40:60) to obtain a high molecular weight silicone resin solution (A2) with a solid content concentration of 20 mass%. Organopolysiloxane LTC755 is an organopolysiloxane having a vinyl group and a hexenyl group, and is mixed with organopolysiloxane (number average molecular weight: 2,000) having a hydrosilyl group as a crosslinking agent. A release film was obtained in the same manner as in Example 1, except that the high molecular weight silicone resin solution (A2) was used instead of the high molecular weight silicone resin (A2).
[0070] A peel strength test using a standard adhesive tape was carried out on the release films obtained as described above in Examples 1 to 7 and Comparative Example 1. The results are shown in Table 1.
[0071] [Table 1]
Claims
1. A base layer; A release layer provided on at least one surface of the base layer, the release layer comprises a high molecular weight silicone resin (A1) having a number average molecular weight of 300,000 or more and 550,000 or less, and a low molecular weight silicone resin (B1) having a number average molecular weight of 1,000 or more and 100,000 or less, the high molecular weight silicone resin (A1) and / or the low molecular weight silicone resin (B1) being crosslinked with a crosslinking agent which is a polyorganosiloxane having a reactive functional group; the high molecular weight silicone resin (A1) has an alkylene group having 3 or more and 12 or less carbon atoms at a crosslinking point, and does not have an alkylene group having 2 or less carbon atoms at the crosslinking point, The silicon atomic weight in the release layer as measured by fluorescent X-ray analysis is 4 kcps or more and 40 kcps or less; A release film characterized in that in the release layer, the content of the low molecular weight silicone resin (B1) is 6 parts by mass or more and 9.8 parts by mass or less relative to 10 parts by mass in total of the high molecular weight silicone resin (A1) and the low molecular weight silicone resin (B1).
2. 2. The release film according to claim 1, wherein a standard acrylic adhesive tape TESA7475 is attached to the release layer in an environment of a temperature of 10 to 30° C. and a relative humidity of 30 to 80% RH, and then the tape is left to stand for 20 hours, and then a peel test is performed in an environment of a temperature of 18 to 22° C. and a relative humidity of 61 to 69% RH, in which the tape is peeled at 170° at a tensile speed of 300 mm / min., and the peel force F1 is 100 mN / 25 mm or less.
3. 3. The release film according to claim 1 or 2, wherein a standard acrylic adhesive tape TESA7475 is attached to the release layer in an environment of a temperature of 10 to 30° C. and a relative humidity of 30 to 80% RH, and then allowed to stand for 20 hours, and then a peel test is performed in an environment of a temperature of 18 to 22° C. and a relative humidity of 61 to 69% RH, in which a peel force F2 is 5.0 N / 25 mm or less in a peel test in which a 20° peel is performed at a tensile speed of 10,000 mm / min.
4. 4. The release film according to any one of claims 1 to 3, wherein a standard acrylic adhesive tape, Nitto 31B, is attached to the release layer in an environment of a temperature of 10 to 30° C. and a relative humidity of 30 to 80%, and then the tape is allowed to stand for 20 hours. After that, in an environment of a temperature of 18 to 22° C. and a relative humidity of 61 to 69% RH, a peel force F3 (N / 25 mm) in a peel test in which 170° peeling is performed at a tensile speed of 1,500 mm / min and a tensile speed of 30,000 mm / min is performed, and a peel force F4 (N / 25 mm) in a peel test in which 170° peeling is performed at a tensile speed of 30,000 mm / min satisfy the following formula (1): F4 / F3≦4.0...(1)
5. 5. The release film according to claim 1, further comprising an anchor coat layer between the base layer and the release layer.
6. A step of preparing a coating liquid by mixing a high molecular weight silicone resin (A2) having a number average molecular weight of 300,000 or more and 550,000 or less, a low molecular weight silicone resin (B2) having a number average molecular weight of 1,000 or more and 100,000 or less, a catalyst, a crosslinking agent which is a polyorganosiloxane having a hydrosilyl group, and an organic solvent; A step of applying the coating liquid to one surface of a substrate layer to form a coating film; and A step of curing the coating to form a release layer, In the coating liquid, the content of the low-molecular-weight silicone resin (B2) is 6 parts by mass or more and 9.8 parts by mass or less relative to 10 parts by mass in total of the high-molecular-weight silicone resin (A2) and the low-molecular-weight silicone resin (B2), The method for producing a release film, wherein the high molecular weight silicone resin (A2) has an alkenyl group having 3 or more and 12 or less carbon atoms, and does not have an alkenyl group having 2 or less carbon atoms.
Citation Information
Patent Citations
Method for manufacturing laminate
JP2001171048A
Mold release film for molding ceramic green sheet
JP2006289670A
Polyester film for double-sided self-adhesive sheet without substrate
JP2012025891A
Release sheet and method of manufacturing release sheet
JP2015193171A
Release film
JP2016198924A
